Graphene field-effect transistor simulation with TCAD on top-gate dielectric influences - Muhamad Amri Ismail; Khairil Mazwan Mohd Zaini; Mohd Ismahadi Syono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents the influence of top-gate dielectric material for graphene field-effect transistor (GFET) using TCAD simulation. Apart from silicon-based dielectric that is typically used for top-gate structure, other high-dielectric constant (high-k) dielectric materials namely aluminum oxide and hafnium oxide are also involved in the analysis deliberately to improve the electrical properties of the GFET. The unique GFET current-voltage characteristics against several top-gate dielectric thicknesses are also investigated to guide the wafer fabrication engineers during the process optimization stage. The improvement to critical electrical parameters of GFET in terms of higher saturation drain current and greater on/off current ratio shows that the use of high-k dielectric material with very thin oxide layer is absolutely necessary.